A Coronary–Pulmonary Artery Fistula with Giant Aneurysm in a Child with Ventricular Septal Defect with Pulmonary Atresia. Issue 4 (24th December 2013) - Mahimaiha, Jayaranganath; Patra, Soumya; Mandikal Kodanda Rama Sastry, Usha; Subramaniam, Anand; Agrawal, Navin; Nanjappa, Manjunath Cholenahally
Mini‐Abstract Pulmonary atresia with ventricular septal defect accounts for about 2% of all congenital heart diseases. Aortopulmonary collaterals are the usual source of pulmonary blood flow. Coronary–pulmonary artery fistula is a rare and sole source of pulmonary blood flow. We are reporting a case of a 6‐year‐old girl who presented with severe cyanosis, clubbing, and effort intolerance. Echocardiography demonstrated a large subaortic ventricular septal defect and pulmonary atresia with confluent pulmonary arteries. It also revealed the presence of a coronary–pulmonary artery fistula along with a giant coronary artery aneurysm. These findings were confirmed by an aortic root angiogram. She was referred for intra‐ cardiac repair.